An evaluation of merits of total hip arthroplasty done for traumatic and non-traumatic displaced fracture neck of femur - Agarwal, Vipul; Dhanda, Manjeet Singh; Singh, Abhishek; Madan, Harnam Singh; Goel, Shewtank; Agarwal, Sarina; Goyal, Pooja (International Journal of Research in Medical Sciences, 2016)
Background: There is ongoing controversy about the relative merits of different types of arthroplasty among specific groups of patients. Paucity of quality data provides an opportunity for extension of this debate. The aim of this study was planned to evaluate merits (outcomes and complications) of total hip arthroplasty done for traumatic and non traumatic displaced fracture neck of femur. Methods: A comparative evaluation was undertaken among 50 patients who underwent total hip replacement at a tertiary care center. A retrospective cohort of fifty patients treated with total hip replacement for traumatic causes of displaced fracture neck of femur (25 patients) and non-traumatic causes of displaced fracture neck of femur (25 patients) were included in this study. The inclusion criteria’s for the traumatic group were acute displaced fracture neck of femur above 50 years and fracture neck with fracture head with dislocation above 50 years. Patients having nonunion fracture neck of femur, failed cancellous screw fixation, intertrochantric fractures and associated acetabulum fractures were excluded from this study. Results: On clinical and functional evaluation, patients scored 84% excellent/good in non-traumatic group whereas 68% excellent/good score in traumatic group. 12% and 16% patients scored poor in non-traumatic group and in traumatic group respectively. In non-traumatic group, following complications were observed. Dislocation rate of 4% (one hip), 4% incidence of aseptic acetabular loosening (one hip), and 16% incidence of heterotrophic ossification (four hips). In traumatic group, we observed 2 (8%) dislocations, 4 (16%) heterotopic ossifications. Loosening of acetabulum and subsidence were observed in two (8%) patients. Conclusions: There are higher chances of dislocation among patients undergoing total hip replacement for a traumatic indications as compared to their non-traumatic indications. Chances of dislocation can be curtailed by keeping known factors in mind along with careful patient selection, adherence to postoperative protocol and use of a lateral approach with large head in high risk patients.